Anxiety and Depression and Associated Factors Among a Sample of Semi-Rural High School Students in Georgia - Raul Perez Zarate; Yi-Ting Hana Lee; Jean A. Welsh; Julie A. Gazmararian (Georgia Southern University, 2023)
Background: Anxiety and depression can affect adolescents' health and current literature lacks studies of youths living in non-urban settings. Methods: We used chi-square and t-tests on data collected from self-administered online surveys, completed by 9th-grade students (n=222) attending a large, semi-rural public high school in the state of Georgia, to assess the prevalence of symptoms of anxiety and depression and associated factors. Results: Almost half of the students self-reported anxiety (43%) or depression (55%) and students who self-reported either condition were more likely to report poorer sleep hygiene, sleepiness, race-related mistreatment, and higher stress. Conclusions: Our findings suggest that symptoms of anxiety and depression are prevalent among youths in semi-rural settings and further research is needed to understand the role of modifiable risk factors and identify effective interventions. Keywords: adolescent mental health; adolescent sleep; anxiety; depression; semi-rural